Human Capital and Climate Change - Noam Angrist; Kevin Winseck; Harry Anthony Patrinos; Joshua Graff Zivin (Global Labor Organization (GLO), 2023)
Addressing climate change requires individual behavior change and voter support for proclimate policies, yet surprisingly little is known about how to achieve these outcomes. This paper estimates causal effects of additional education on pro-climate outcomes using new compulsory schooling law data across 16 European countries. It analyzes effects on pro-climate beliefs, behaviors, policy preferences, and novel data on voting for green parties - a particularly consequential outcome to combat climate change. Results show a year of education increases pro-climate beliefs, behaviors, most policy preferences, and green voting, with voting gains equivalent to a substantial 35% increase.
Keywords: D72; H41; I20; I28; P16; Q01; Q5; 330; Human Capital; Education; Climate Change; Compulsory Schooling Laws; Voting